Effect of authentic chemistry problem solving competency in solving open-ended problems - Suraiya Muhamad, 1971- author; Jamalludin Harun, supervisor; Johari Surif, supervisor; Noor Dayana Abd. Halim; Fakulti Pendidikan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Pendidikan Kimia)) - Universiti Teknologi Malaysia, 2018